Sustainable Desert Traditional Architecture of the Central Region of Saudi Arabia. (30th March 2016) - Mortada, Hisham
Abstract: For thousands of years mud houses have represented the practical wisdom and spirituality of people, particularly those of desert regions, who learned how to use local materials to build homes that fitted the environmental and cultural conditions, in which they lived. As a case study, the central region of Saudi Arabia exhibits a tradition of earth architecture that is unique in style, culture and sustainability. Aiming to contribute towards the local debate of the suitability of the traditional mud architecture for today's lifestyle of Saudis, this paper explores the sustainable nature of the traditional adobe architecture of this hot arid region from environmental, social and technical points of view. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment